2019
DOI: 10.3390/lubricants7080068
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Surface Texturing on the Frictional Behaviour in Starved Lubricated Parallel Sliding Contacts

Abstract: Starvation occurs when the lubricated contact uses up the lubricant supply, and there is not enough lubricant in the contact to support the separation between solid surfaces. On the other hand, the use of textures on surfaces in lubricated contacts can result in a higher film thickness. In addition, a modification of the surface’s geometrical parameters can benefit the tribological behaviour of the contacts. In this article, for parallel sliding surfaces in starved lubricated conditions, the effect of surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Surface modification can provide significant control over the specific biological responses of biomaterials used in dental implants around the cell tissues [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Several studies have demonstrated that micro-and nanoscale topographic biomaterials are beneficial for protein absorption, cell adhesion, proliferation, and antibacterial activity [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface modification can provide significant control over the specific biological responses of biomaterials used in dental implants around the cell tissues [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41]. Several studies have demonstrated that micro-and nanoscale topographic biomaterials are beneficial for protein absorption, cell adhesion, proliferation, and antibacterial activity [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that surface textures are an effective method for reducing bacterial behavior at interfaces [28][29][30]. Several successful attempts have been made to study the antibacterial behavior of dental materials using laser surface texturing methods [14,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of manufacturing processes have been developed and evaluated for structuring engineering surfaces at the microscale. Applications range from modifying tribological properties, for which the relationship between friction and surface textures is researched [1,2], to inducing hydrophobicity by microstructuring surfaces [3], where contact angle measurements are used to assess the hydrophobicity or hydrophilicity of the surfaces. Convex microstructural features might offer additional advantages in this context [4].…”
Section: Introductionmentioning
confidence: 99%
“…Bijani et al [7] developed a theoretical model to study the effects of surface texturing on the frictional behaviour of parallel sliding contacts under starved lubrication conditions. Applying a deterministic asperity contact model, which considered the effects of different scales of surface features (texture and roughness), it was shown that surface texturing may improve lubricant film formation under the conditions of starvation.…”
mentioning
confidence: 99%